2023
DOI: 10.29333/ejgm/12571
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge, motivation, behaviors, and information sources on antibiotic use and resistance in Jordan

Abstract: <b>Aim:</b> This study aims to examine the nurse knowledge, motivation, and behavior about antibiotics and antibiotic resistance. A secondary objective was to study the preferred information sources used by Jordanian nurses, as well as their knowledge of the information available to promote rational prescription practices in the Jordanian health system.<b> </b><br /> <b>Method: </b>The study was cross-sectional in design and nurses (n=1,093) completed an online survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In contrast, four studies conducted in Asia regarding predictors of attitude, knowledge, and practices among neonatal nurses regarding the MDROs. 34 , 35 , 40 , 41 Firstly, Abuhammad et al 42 in Jordan found that the degree of knowledge was significantly related to the nurses’ age, education, and number of years of experience. Secondly, a study in Pakistan by Hayat et al 35 found a significant correlation between age and years of experience and knowledge of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, four studies conducted in Asia regarding predictors of attitude, knowledge, and practices among neonatal nurses regarding the MDROs. 34 , 35 , 40 , 41 Firstly, Abuhammad et al 42 in Jordan found that the degree of knowledge was significantly related to the nurses’ age, education, and number of years of experience. Secondly, a study in Pakistan by Hayat et al 35 found a significant correlation between age and years of experience and knowledge of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Irrational antibiotic prescribing is a major contributor to the worldwide rise in ABR among children, which in turn can lead to more cases of potentially fatal infections, more complicated medical conditions, and even death in some cases and mostly among children [7,10,11]. If no action was taken to decrease the spread of ABR, it is estimated that ABR will kill around 700,000 people each year by 2050 [12].…”
Section: Introductionmentioning
confidence: 99%